Natural Pigment –Poly Vinyl Alcohol Nano composites Thin Films for Solar Cell: nanocomposites thin film (Baghdad Science Journal, 2020)
Solar cells thin films were prepared using polyvinyl alcohol (PVA) as a thin film, with extract of natural pigment from local flower. A concentration of 0.1g/ml of polyvinyl alcohol solution in water was prepared for four samples, with various concentrations of plant pigment (0, 15, 25 and 50) % added to each of the four solutions separately for preparing (PVA with low concentrated dye , PVA with medium concentrated dye and PVA with high concentrated dye ) thin films respectively . Ultraviolet absorption regions were obtained by computerized UV-Visible (CECIL 2700). Optical properties including (absorbance, reflectance, absorption coefficient, energy gap and dielectric constant) via UV- Vis were tested, too. Fourier transform infrared (FTIR) spectrophotometer was employed to test the samples. Thermal analysis of thin films, including melting point (Tm), onset degree, endset degree, and crystallinity% were tested by differential scanning calorimeter (DSC). Three dimensional morphologies of thin films were inspected by atomic force microscopy (ATM). Contact angle also was tested as an index to hydrophilicity. Results proved that the ultraviolet and FTIR absorption increase after adding the natural pigment to PVA thin film, as well as it increases with increasing concentration of natural pigment. DSC analysis revealed an increase of PVA melting point when adding 15% concentration and it decreases with a 50% concentration of pigment. AFM results show an increase in surface roughness, hence the surface bearing index of PVA thin films is inversely proportional to pigment concentration. Contact angle decreases from 46.5° for pure PVA thin film to 44. 8°, 42. 6° and 35.2° after adding (15, 25, and 50)% concentration of natural dye respectively. Optical properties were enhanced by adding the natural dye, hence energy gap decreased from 3 eV for pure PVA to 2.3 eV for the PVA with a high concentrate dye. Dielectric constant increased with increasing concentration of dye, which leads to high polarization of solar cell.